Zika Virus in Rectal Swab Samples - Bôtto-Menezes, Camila Helena Aguiar (Emerg Infect Dis, 2019)
We detected Zika virus RNA in rectal swab samples from 10 patients by using real-time reverse transcription PCR, and we isolated the virus from 1 patient. The longest interval from symptom onset to detection was 14 days. These findings are applicable to diagnosis and infection prevention recommendations.